Modification of Levels of Adhesion Molecule Expression of Human Innate Immune Cells by Glycopolymers of Marine Bacteria - T. P. Smolina; T. S. Zaporozhec; N. N. Besednova (Антибиотики и Химиотерапия, 2020)
By flow cytometry it was demonstrated that lipopolysaccharide and exopolysaccharide of marine proteobacteria Pseudoalteromonas nigrifaciens alter the expression of adhesion molecules on human neutrophils and monocytes, reducing the expression level of molecules CD62L and increasing the expression of CD11b, CD11c and CD54.